Is the selfish life-cycle model more applicable in Japan and, if so, why? A literature survey - Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2020)
The selfish life-cycle model or hypothesis is, together with the dynasty or altruism model, the most widely used theoretical model of household behavior in economics, but does this model apply in the case of a country like Japan, which is said to have closer family ties than other countries? In this paper, we first provide a brief exposition of the simplest version of the selfish life-cycle model and then survey the literature on household saving and bequest behavior in Japan in order to answer this question. The paper finds that almost all of the available evidence suggests that the selfish life-cycle model applies to at least some extent in all countries but that there is more consistent support for this model in Japan than in the United States and other countries. It then explores possible explanations for why the life-cycle model is more consistently supported in Japan than in other countries, attributing this finding to government policies, institutional factors, economic factors, demographic factors, and cultural factors. Finally, it shows that the findings of the paper have many important implications for economic modeling and for government tax and expenditure policies.
Keywords: D11; D12; D14; D15; D64; E21; J14; 330; Age structure; altruism; bequest motives; borrowing constraints; consumption; culture; dissaving; dynasty model; elderly; family ties; household saving; inheritances; intergenerational transfers; Japan; life-cycle model; religiosity; retirement; Ricardian equivalence; saving motives; selfishness; social norms